High-Value Natural Resources-Smuggling-National Security Nexus: The Case of Zimbabwe in the Fourth Industrial Revolution and Beyond (Journal of Governance and Development (JGD), 2018)
Smuggling of high-value natural resources is a high risk of Zimbabwean national security. Smugglers are devising complex and sophisticated means to evade ofï¬cial scrutiny in their smuggling activities. The porous nature of Zimbabwean borders is a common African problem. These borders enable the illegal transgression of international laws against the transportation of goods, substances and even people across borders. In recent years Zimbabwe has been awash with smuggling of ivory, diamonds and gold which are high-value natural resources. This has provoked this opinion research paper on smuggling of natural resources and its impact on national security. The objectives of the research were to explain the nature of smuggling of high-value natural resources and its likely impacts in Zimbabwe. Research questions formulated focused on the nature of smuggling, the role of technology to curb smuggling of high-value natural resources and threats to national security. The paper also assesses how technological improvements in the fourth industrial era can be harnessed to curb the smuggling. A study of secondary literature on smuggling, national security and natural resources was done. This has enabled this opinion paper on the role of technology in the fourth industrial age in safeguarding natural resources in Zimbabwe. Zimbabwe is at risk of smuggling and the threats associated due to porous borders.